A Systematic Review of Criteria-Led Patient Discharge. Issue 2 (April 2019) - Lees-Deutsch, Liz; Robinson, Jane
Abstract : Background: This article reports on a systematic review conducted to critique safety, quality, length of stay, and implementation factors regarding criteria-led discharge. Purpose: Improving patient flow and timely bed capacity is a global issue. Criteria-led discharge enables accelerated patient discharge in accordance with patient selection. Methods: A systematic review was conducted to identify literature on criteria-led discharge from 2007 to 2017. The quality of articles was appraised using a tool for disparate studies. Two reviewers extracted relevant data independently. Results: Fifteen studies were identified that showed no increase in patient readmission or complication rates with criteria-led discharge, demonstrating patient safety. The quality of the patient discharge was unremarkable. None of the studies showed an increase in length of stay. Conclusions: The safety, quality, and length of stay for patients discharged through criteria-led discharge are inextricably linked to the process adopted for its implementation. Abstract : Supplemental Digital Content is Available in the Text.